Development of a Perspective Metal Hydride Energy Accumulation System Based on Fuel Cells for Wind Energetics - Yurii M. Matsevytyi; Natalia A. Chorna; Andrii A. Shevchenko (Journal of Mechanical Engineering, 2019)
Hydrogen is one of the most energy-intensive and environmentally friendly energy carriers, which is why its use for the operation of fuel cells (FCs) makes it possible to create efficient autonomous energy supply systems. Power plants based on fuel cells are characterized by high efficiency and environmental safety. Of particular interest are power plants based on low-temperature alkaline FCs with a capacity of 1 to 20 kW, because they can be widely used as autonomous power sources for residential consumers. The location of such autonomous installations is assumed to be in close proximity to the energy consumer, which requires that fuel supply systems be highly safe, reliable and environmentally friendly. These requirements are met by hydrogen storage systems based on reversible metal hydrides (MH), capable of absorbing and releasing hydrogen. One of the main components of an autonomous energy supply system is a multiple-action hydrogen metal hydride storage battery. For the efficiency of the "FC - MH hydrogen storage" system, it is necessary to develop a methodology for determining its main technical characteristics both at the stage of creation and in the process of studying these characteristics. The article presents the developed scheme of a wind power plant with a hydrogen energy storage battery, solves the problem of selecting the FC, and analyses the operation of the fuel cell with the MH hydrogen storage system. The results obtained allowed us to determine the pattern between the amount of heat taken from the FC for hydrogen desorption with its subsequent use to increase the power of the FC, and ensure the characteristics of the consumer network. It is shown that the use of an integrated approach to the study of a perspective scheme of accumulation and use of wind energy will solve the problem of smoothing the irregularity of energy supply from renewable sources.